Factors influencing teaching choice as predictors of Teacher Identity in prospective Special Education teachers - Fuentes, Lidia Valdenegro; Gonzalez Sanzana, Alvaro (My University, 2024)
Teacher identity has been studied as a broad construct, mutable and influenced by multiple factors during its development. Few investigations have addressed the factors that could explain teacher identity during Special Education teacher education. The objective was to establish the explanatory capacity of motivational and perceptual factors for career choice on teacher identity. A quantitative approach with an explanatory cross-sectional design was used. 180 Special Education preservice teachers from 10 Chilean universities participated in the study. The FitChoice Scale and Teacher Identity Measurement Scale were used. The data were analysed with Bayesian linear regression. The results show that perception factors alone explain 32% of the behaviour of teaching identity. Meanwhile, the joint model between motivation factors, perception factors for career choice, and sociodemographic variables such as family income and having a teaching family member shows a greater explanatory capacity concerning teaching identity (38%). It is hoped that the results of this research constitute an approximation to the explanation of the factors that influence the development of teaching identity in future Special Education teachers.
Keywords: teacher; special education teacher education; motivation; perception